KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA MENGAJAR GURU - Liza Ervina; Wahyudi Wahyudi; M. Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractA principal is a leader in the school. As a leader, a principal should have had three basic competencies i.e : mobilizing, directing and guiding competency. Those three basic competencies is needed to obtain the goals in education. The first  is directing competency. It is an ability to shown to the teachers  and staff how to do their work correctly. With this ability, the principal helped the teachers and staff to improve their competencies. Next is mobilizing competency. This abilitu allowed the principal to persuade the teachers, staff and students to do their work voluntary without coercion. The principal have to improve teachers and staff competencies as well as students motivation Teachers competencies is habitual action. It explained in process of teaching and learning in the class and also in the activities. A competence teacher should be able to manage the activities i.e : 1. Pre Teaching  2. Teaching  3. Post teaching  4. Teacher involvement. Teacher Competency is the important things in education. Here are three educational aspect i.e : teacher ability to make a plan teaching and learning process. Keywords   : Principal Leadership and Teacher competency.